2017
DOI: 10.3164/jcbn.17-21
|View full text |Cite
|
Sign up to set email alerts
|

Sake lees hydrolysate protects against acetaminophen-induced hepatotoxicity via activation of the Nrf2 antioxidant pathway

Abstract: Acetaminophen is a commonly used analgesic. However, an overdose of acetaminophen causes severe hepatotoxicity via depletion of hepatic glutathione. Here, we investigated the protective effects of sake lees hydrolysate against acetaminophen-induced hepatotoxicity in mice. Sake lees hydrolysate was administered orally to ICR mice for seven days. Six hours after acetaminophen treatment, the mice were sacrificed, and blood and liver samples were collected for analysis. Treatment with acetaminophen markedly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…028-002), and the study was conducted according to the Animal Experimentation Guidelines of Shujitsu University. The procedures were performed as described in our previous publications. , Mice were randomly divided into five groups. The rice peptide groups were orally administered OP60 (250 or 500 mg/kg body weight) via a stomach tube daily for 7 days, whereas the control and APAP groups were administrated saline.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…028-002), and the study was conducted according to the Animal Experimentation Guidelines of Shujitsu University. The procedures were performed as described in our previous publications. , Mice were randomly divided into five groups. The rice peptide groups were orally administered OP60 (250 or 500 mg/kg body weight) via a stomach tube daily for 7 days, whereas the control and APAP groups were administrated saline.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…17 Additionally, rice-derived peptides and sake lees hydrolysate are hepatoprotective in the case of acetaminophen (APAP)-induced liver injury. 18,19 These antioxidative effects were suggested to be mediated through the Nrf2 antioxidant pathway. However, only a few peptides have been shown to act as indirect antioxidants by regulating the oxidative defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 expression contributes to protection against APAP-induced liver damage.‍ ( 12 ) In previous reports, sulforaphane,‍ ( 36 ) sake lees hydrolysate,‍ ( 37 ) and salvianolic acid C ‍ ( 38 ) have protective effects against APAP-induced hepatotoxicity through antioxidant effects mediated via HO-1 induction. We previously reported that RP protects against APAP-induced hepatotoxicity in mice.‍ ( 22 ) Our results indicate that RSAVLLSH derived from RP may be an active peptide with a hepatoprotective effect via the induction of HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of HO-1 is to degrade heme and generate carbon monoxide (CO) and biliverdin which are both powerful antioxidants (36). According to previous reports, sulforaphane (37), sake lees hydrolysate (38), and salvianolic acid C (34) play protective roles against APAP-induced hepatotoxicity though antioxidant effects mediated by HO-1 induction. YCE induced HO-1 expression in mice livers (Fig.…”
Section: Discussionmentioning
confidence: 99%